Redox effects of low-spin Ru(ii/iii) on slow magnetic relaxation of Ru–Mn(iii) 1D cyanide-bridged complexes. Issue 22 (24th May 2017) - Zhu, Xiaoquan; Su, Shaodong; Cao, Wenhai; Wen, Yuehong; Hu, Shengmin; Wu, Xintao; Sheng, Tianlu
Abstract : Redox active Ru-based cyanide bridges Mn(iii ) fragments with different oxidation states and forms two new 1D compounds, of which one shows simple paramagnetism and another shows slow magnetic relaxation. Abstract : A new one-dimensional cyanide-bridged complex [Mn III (salphen)Ru II (DMAP)4 (CN)2 ](PF6 ) (1 ) and its oxidized derivative [Mn III (salphen)Ru III (DMAP)4 (CN)2 ](PF6 )2 (2 ) have been synthesized and fully characterized. Magnetic measurements showed that1 shows simple paramagnetism but2 shows intrachain ferromagnetic interaction with slow magnetic relaxation.